Ribosome hopping and translational frameshifting are inadequate alternatives to translational attenuation in cat-86 regulation. - Rogers, E J (1991)
The induction of cat-86 by chloramphenicol has been proposed to follow the translational attenuation model. In the absence of inducer, the cat-86 gene is transcribed but remains phenotypically unexpressed because the transcripts sequester the ribosome binding site for the cat coding sequence in a stable stem-loop structure, preventing translation initiation. The translational attenuation model proposes that the natural inducer, chloramphenicol, stalls a ribosome in the leader region of cat transcripts, which causes localized melting of the downstream stem-loop structure, allowing initiation of translation of the cat-86 coding sequence. Although it is established that ribosome stalling in the cat-86 leader can induce translation of the coding sequence, several subsequent steps predicted by the model remain to be experimentally confirmed. As a consequence, the present evidence for cat-86 regulation can also be explained by two other potential control devices, ribosome hopping and translational frameshifting. Here we describe experiments designed to determine whether the alternatives to translational attenuation regulate cat-86. The results obtained are inconsistent with both competing models and are consistent with predictions made by the translational attenuation model.